2022
DOI: 10.3390/nano12050774
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Gas Sensors Based on V3S4 Monolayer

Abstract: Novel magnetic gas sensors are characterized by extremely high efficiency and low energy consumption, therefore, a search for a two-dimensional material suitable for room temperature magnetic gas sensors is a critical task for modern materials scientists. Here, we computationally discovered a novel ultrathin two-dimensional antiferromagnet V3S4, which, in addition to stability and remarkable electronic properties, demonstrates a great potential to be applied in magnetic gas sensing devices. Quantum-mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…The proposed structure 1A 0 is characterized by a distorted trigonal bipyramidal local environment of the TM atom, which should make this structure more metallic because of the degenerated d orbitals. The square-pyramidal environment in 1A 000 with the TM atom on the facet suggests the possibility for the application of this structure for molecular sorption and detection (Chepkasov et al, 2022). We believe that the proposed variety of phases of Janus TMDs in the future can significantly expand the scope of their application.…”
Section: Discussionmentioning
confidence: 92%
“…The proposed structure 1A 0 is characterized by a distorted trigonal bipyramidal local environment of the TM atom, which should make this structure more metallic because of the degenerated d orbitals. The square-pyramidal environment in 1A 000 with the TM atom on the facet suggests the possibility for the application of this structure for molecular sorption and detection (Chepkasov et al, 2022). We believe that the proposed variety of phases of Janus TMDs in the future can significantly expand the scope of their application.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, several metastable TMD phases have been theoretically proposed, among which are the square-octagonal (S) and disordered square-octagonal (S’) monolayers [ 4 ], another hexagonal H’ phase [ 5 ], and a triclinic-structured A’ phase [ 6 , 7 ]. Moreover, several non-stoichiometric monolayers in the M-X system have been proposed [ 8 , 9 , 10 , 11 ] and some of them successfully fabricated [ 12 , 13 ]. The above indicate the prospects of the search for and investigation of new monolayer structures in the M-X systems that can be produced from non-van der Waals crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is an alternative approach which is the search for new phases of TMDs having less density than H-MoS 2 monolayers because bulk TMDs can exist not only in the hexagonal 2H phase but also in trigonal 1T and rhombohedral 3R polymorphs [38]. Moreover, recent investigations showed that transition-metal chalcogenides can form various monolayered structures [39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%